OSTEOPONTIN, INTERLEUKIN-15 AND DYSFUNCTION OF LEFT VENTRICULAR MYOCARDIUM IN HYPERTENSIVE PATIENTS WITH CHRONIC HEART FAILURE - Kovalyova, O. M.; Kozhemiaka, G. V.; Honchar, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Based on a survey of 108 patients with hypertension complicated by chronic heart failure, studied the connection concentration of osteopontin, interleukin-15 inserum and morpho-functional characteristics of the left ventricle of the heart. In patients with CHF osteopontin levels were significantly higher, it revealed a relationship between adverse LV filling state and knots in serum osteopontin, while the level of IL-15 did not show such a relationship. The results indicate the potential value of osteopontin as a biomarker for the diagnosis of CHF.1. In hypertensive patients in combination with CHF revealed significantly elevated levels of osteopontin in the blood serum, reaching maximum severity in patients with heart failure stage II. IL-15 level in these patients does not depend on the presence and severity of heart failure. 2. Increased serum levels of osteopontin in hypertensive patients is associated with a relatively unfavorable LV filling state, both in the early and late in diastole, the manifestation of which is the negative correlation with the values of osteopontin peak E, and a positive attitude to the E/E'. 3. The established relationship concentration of osteopontin in the blood serum with functional myocardial changes in hypertensive patients complicated with heart failure, an opportunity to recognize the important role of this maker of fibrosis in myocardial remodeling and heart failure severity.